Regulation of V-ATPase Assembly in Nutrient Sensing and Function of V-ATPases in Breast Cancer Metastasis - Collins, Michael P.; Forgac, Michael (Frontiers in Physiology, 2018)
V-ATPases are proton pumps that function to acidify intracellular compartments in all eukaryotic cells, and to transport protons across the plasma membrane of certain specialized cells. V-ATPases function in many normal and disease processes, including membrane traffic, protein degradation, pathogen entry and cancer cell invasion. An important mechanism of regulating V-ATPase activity in vivo is regulated assembly, which is the reversible dissociation of the ATP-hydrolytic V1 domain from the proton-conducting V0 domain. Regulated assembly is highly conserved and occurs in response to various nutrient cues, suggesting that it plays an important role in cellular homeostasis. We have recently found that starvation of mammalian cells for either amino acids or glucose increases V-ATPase assembly on lysosomes, possibly to increase protein degradation (for amino acid homeostasis) or for the utilization of alternative energy sources (during glucose starvation). While regulation of assembly in response to amino acid starvation does not involve PI3K or mTORC1, glucose-regulated assembly involves both PI3K and AMPK. Another important form of V-ATPase regulation is the targeting of the enzyme to different cellular membranes, which is controlled by isoforms of subunit a. We have shown that V-ATPases are localized to the plasma membrane of highly invasive breast cancer cells, where they promote cell migration and invasion. Furthermore, overexpression of the a3 isoform is responsible for plasma membrane targeting of V-ATPases in breast tumor cells leading to their increased invasiveness.